Bioaumentação in situ em solo residual de basalto contaminado com biodiesel - Bonatto, Jaqueline (2013)
Contamination of soil and groundwater by petroleum hydrocarbons has been subject of concern throughout the world in recent decades. The tank leaks and accidental spills on highways are the main causes of soil contamination. The contact of these substances with the medium provides both human health risk for the environment. This research aims to evaluate will evaluate the degradation of biodiesel in soil using the technique of in situ bioaugmentation. The study involved the following steps: designing and assembling the equipment, test pilot, will be analyzed quantitatively, by analyzing oil and grease, and qualitatively, the degradation of carbon chains by gas chromatography, and, moreover, will be evaluated influence of moisture and pH in the three spoke and six depths, and performed the microbial count by NMP. To test of bioremediation, soil samples were molded no deformation removed to an average depth of 1.20 m with cylindrical shape of 300 mm height and 300 mm in diameter. The analyzes were evaluated in five determined times 0, 15, 30, 60 and 90 days of contamination. The CP were maintained at laboratory temperature. The dispersion of bioaugmentation occurred homogeneously in CP, and extraction of the contaminant was approximately 60% in 60 days. The assembled equipment mounted proved of great importance. Satisfactory results indicated good application of the technique of in situ bioaugmentation